Pemanfaatan Teknologi Dan Desain Untuk Pengembangan Referensi Pembelajaran Nirmana Trimatra Untuk Peningkatan Kompetensi Mahasiswa (Studi Kasus Mahasiswa Prodi Sendratasik UPR) - Muh Andis Hidayatullah; Nawung Asmoro Girindraswari; Utari Yolla Sundari (Student Scientific Creativity Journal, 2023)
The ability to understand and utilize technology, especially for learning media, is very supportive in learning more creative Tridimensional designs. Information Technology is a method that should be used in the learning process, it is hoped that it will optimize the learning of fine arts in the Sendratasik study program. The purpose of this research is to develop references for learning the three-dimensional nirmana and increase the competence of students in the Sendratasik Study Program at the University of Palangka Raya in learning fine arts, namely the tri-dimensional nirmana. In this study used the Research and Development (R&D) method. The Research and Development stage is the development of learning references by making tridimensional nirmana infographics using the Canva application. Until a nirmana infographic design is produced. Then the Development stage is continued by presenting the results of the infographic design through a workshop to determine the level of student understanding of the three-dimensional nirmana learning references.